Adjuvant high-dose-rate interstitial brachytherapy for malignant peripheral nerve sheath tumor of the foot: a case report - Vavassori, Andrea; Pennacchioli, Elisabetta; Augugliaro, Matteo; Durante, Stefano; Dicuonzo, Samantha; Marco Orsolini, Gian; Prestianni, Pierpaolo; Cambria, Raffaella; Comi, Stefania; Mazzarol, Giovanni; Cattani, Federica; Lazzari, Roberta; et al. (Journal of Contemporary Brachytherapy, 2021)
Soft tissue sarcomas of the foot are extremely rare and can therefore be misdiagnosed as benign diseases, and be prematurely removed with an unplanned excision. The standard treatment is a wide local excision with an addition of radiotherapy as an alternative to a radical resection (e.g., below-knee or foot amputation). We report on a patient with primary malignant peripheral nerve sheath tumor in the foot plantar soft tissue, who had no evidence of the disease and no severe late toxicity higher than grade 2, 40 months after receiving amputation of toes and adjuvant interstitial high-dose-rate brachytherapy (HDR-BT). To the best of our knowledge, only a few cases were treated with HDR-BT with this scenario. From our findings, HDR-BT could be a safe and quick treatment option for these types of lesions.